The coming of age for paid digital campaigning: equalization or normalization in the 2019 Belgian federal elections? - Vanden Eynde, Gunther; Put, Gert-Jan; Maddens, Bart (Online information review, 2023)
PurposePaid digital campaigning tools play an increasingly pivotal role in individual election campaigns worldwide. Extant literature often juxtaposes the equalization theory, which argues that these tools create a level playing field, and the normalization theory, which contends that strong and resource-rich politicians benefit most from digital tools. This article aims to inform this debate by looking at it from a campaign expenditure perspective beyond the Anglo-American bias of most research on the subject.Design/methodology/approachThe authors use an original dataset on campaign expenditures and resources of 1,798 candidates running for 13 Belgian parties in the 2019 federal parliamentary election. Relying on multilevel statistical models, the authors link the candidates' digital campaign expenses to their incumbency status, which is expected to affect digital campaigning.FindingsWhile earlier work on majoritarian cases often showed contradicting results, this study on the Belgian flexible-list proportional representation (PR) case provides strong support for the equalization theory by demonstrating that incumbents are not only less inclined to spend on digital tools than challengers, but also spend a smaller part of their budget on these tools.Originality/valueThis paper contributes to the literature by exploring the equalization versus normalization debate from a campaign expenditure perspective using a made to purpose dataset in a non-Anglo-American context.Peer reviewThe peer review history for this article is available at: https://publons.com/publon/10.1108/OIR-12-2021-0679